PENDUGAAN KESUBURAN PERAIRAN BERDASARKAN SEBARAN NUTRIEN DAN KLOROFIL-a DI TELUK KENDARI SULAWESI TENGGARA - Nur Irawati (Jurusan Perikanan dan Kelautan, 2014)
Eutrofication is an increase of nutrient supply (nitrogen and phosphor) to a very high concentration and above the limit that the nature can cope with. This recent research was aimed to predict the eutrofication of the waters based on the distribution of nutrients and chlorophyll-a and conducted on November 2012. The research was carried out by considering two main parameters which were main research parameters and supporting parameter over physical, chemical and biological variables. The main research parameters consisted of total N and P, chlorophyll-a and dissolved oxygen of which those variables were the main variables used in the TRIX index analysis (an index used to characterized the trophic status of a body of waters). The fertility status of Kendari Bay based on TRIX index was categorized as eutrophic having TRIX index of 5.12. It is confirmed that the level of nutrient (TN and TP), chlorophyl-a and water clarity determines the fertility status of a water body ranging from oligotrophic to hypertrophic.